Pengaruh Brand Image, Brand Awareness, dan Electronic Word of Mouth terhadap Keputusan Pembelian Sunscreen Azarine di Kota Banjarmasin - Bryan Agusto Diharjo; Lydia Goenadhi (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2025)
This study investigates the impact of brand image, brand awareness, and electronic word- of-mouth (e-WOM) on purchase decisions for Azarine sunscreen products in Banjarmasin City, Indonesia. The research aims to determine whether these variables collectively and individually influence consumers’ choices when selecting Azarine sunscreen. Adopting a quantitative approach, data were collected via structured questionnaires distributed to 150 purposively sampled respondents who had purchased Azarine sunscreen. The hypotheses were tested using multiple linear regression analysis with SPSS. The results reveal that brand image, brand awareness, and e-WOM collectively exhibit a statistically significant influence on purchase decisions (F-value = 0.000, p < 0.05). However, partial analysis demonstrates that only e-WOM has a positive and significant effect (β =0.000, p < 0.05), while brand image and brand awareness show no significant individual impact (p > 0.05). The model explains 30.1% of the variance in purchase decisions (R² = 0.301), indicating that 69.9% of influencing factors—such as pricing, promotions, or personal preferences—remain unexamined. These findings highlight the critical role of e-WOM in driving consumer choices for skincare products in Banjarmasin City, suggesting that marketers should prioritize digital engagement and user-generated content strategies. Further research should explore additional variables to account for the unexplained variance.